2017
DOI: 10.1016/j.amepre.2017.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Combined Healthy Behaviors and Healthcare Services Use in Older Adults

Abstract: The combination of five to six healthy behaviors in older adults is associated with half the risk of polypharmacy and using several healthcare services. In an era of constrained resources in most countries, this information may help inform health policy to control healthcare spending in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 43 publications
3
11
0
1
Order By: Relevance
“…This fi nding supports the study in Northern Nigeria which reported that 75% of hypertensive patients were females [14]. This deduction suggests that women exhibit more health caring attitude and have enough time to visit the clinic than men, this was further supported by cross sectional studies in Spain and the US where similar fi ndings were reported [21,22]. Mean MA Score ± SD 5.7 ± 2.1 subjects in this study were in monogamous marriage.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This fi nding supports the study in Northern Nigeria which reported that 75% of hypertensive patients were females [14]. This deduction suggests that women exhibit more health caring attitude and have enough time to visit the clinic than men, this was further supported by cross sectional studies in Spain and the US where similar fi ndings were reported [21,22]. Mean MA Score ± SD 5.7 ± 2.1 subjects in this study were in monogamous marriage.…”
Section: Discussionsupporting
confidence: 89%
“…This corroborates earlier work done by Lee in China which that women were reported to have higher odds of medication adherence when compared with the men [35]. Several reasons that could probably explain this are that women are more likely to receive fi nancial support from their spouses to cater for themselves among other things and so much so because they utilise health care services more than men [21,22]. However, this fi nding is in contrast with the work done by Shah which found that males are more likely to adhere to antihypertensive medications [36].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…19 Personal health practices (particularly lifestyle behaviors) are equally important predictors of future health care utilization. 63 In this study, a high level of compliance with Australian dietary guidelines was shown to predict CM service use among participants. This is similar to findings from other studies, 44 and it supports the view that CM users are more likely to be active participants in their health care and to demonstrate greater health awareness behaviors than non-CM users.…”
Section: Discussionmentioning
confidence: 74%
“…Tackling the drivers of HCE is an enduring policy concern. Known drivers of overall growth in HCE include behaviours and lifestyle factors such as smoking, diet or physical activity [4], wealth and income effects [5] and prices [6]. There is evidence that demographic factors such as population ageing [7] are associated with rises in HCE.…”
Section: Introductionmentioning
confidence: 99%